Seismic Hybrid Simulation of Stiff Structures: Overview and Current Advances. (27th March 2014) - Bousias, Stathis N.
Abstract : Advances in the area of structural testing have in recent years led to hybrid simulation, that is, the advanced structural experimental method that encompasses the traditional pseudodynamic testing method and relies on substructuring to offer the advantage of combining the actual experimental testing of selected parts of the structure to the numerical treatment of the rest. The experimental part usually involves simplified test setups and structural elements with few degrees of freedom. Thus, issues of cross-coupling present in testing MDOF structures have not been treated adequately so far. In addition, it has been realized that when it comes to testing very stiff structures, in which the above phenomena are accentuated, further problems arise in relation to the quality of actuator control (accuracy of imposed displacements and stability of the test process). Few studies have focused on these issues, thus necessitating more work in the future. The present study provides an overview of the approaches that have been adopted so far, reports on recent advancements, and raises the points in which more research is needed.